Penerapan Metode AHP-SAW Berbasis Web Untuk Menentukan Lulusan Terbaik Di Prodi Profesi Ners UMKT - Any Sawheri Gading; Hamada Zein; Khusnul Khotimah; Adia Lestari; Aulia Khofifah Syamsuri; Siti Patimah; Tri Wahyudi; Joni Saputra; Ilhan Firanda; Achmad Farid; Ferdi Iwanda (Jurnal Ilmiah Dan Karya Mahasiswa, 2024)
In the nursing profession study program, has an important role in producing quality graduates and is ready to compete in the world of work. This research has a high urgency because it can make a real contribution in improving the quality of graduates of the UMKT Ners professional program. The main objective of this research is to implement a web-based AHP-SAW method to determine the best graduates in the UMKT Nursing Profession Program. The data collection method uses secondary data. Secondary data is obtained based on data from related agencies and sources, including the data that has been collected. This research uses multi-criteria, namely GPA, Study Period, Achievement, and Final Project KIAN. The AHP method is used to determine weights based on many criteria or multi criteria. The results of this study concluded that the implementation of the AHP-SAW method can help determine the best graduates in the UMKT Ners Professional Study Program. This system is equipped with features that can display all calculations in detail, this system also has a database that makes it easy for users to access LifeTime, other advantages can overcome the possibility of lost data. the author hopes that this system will be developed to be dynamic so that it can be used on all devices. As for the appearance of the system which is still basic, it can be developed to be more attractive, but still has to adjust the purpose of using the system.